2018
DOI: 10.1177/0731684418778356
|View full text |Cite
|
Sign up to set email alerts
|

Machining and its challenges on bio-fibre reinforced plastics: A critical review

Abstract: Bio-degradability and sustainability have become major objectives in the field of materials engineering. Due to this, the utilisation of natural reinforcement is gaining immense attention among composite researchers. Among the different composites, polymeric composites are used as structural components. In the present day investigations, bio-elements are majorly utilized as reinforcements due to their properties and bio-degradability. Although polymeric components are manufactured in the shape of the final com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 60 publications
1
25
0
1
Order By: Relevance
“…As output parameters, surface roughness, kerf taper angle, and material removal rate will also be the focus of this survey, as well as the phenomenon of delamination, a summary of the relationship between these two and input parameters. It is noteworthy that the AWJM uses erosion to remove the target material, so there is no contact between the cutting tool and the material, and there are no high impact defects of cutting forces related to delamination damage [ 13 , 18 ], but strength of NFRPs machined by AWJM gets affected, so the tensile strength is somewhat lesser than the composites cut by traditional methods [ 13 ].…”
Section: Cutting Processes Of Natural Fiber-reinforced Polymer Commentioning
confidence: 99%
See 1 more Smart Citation
“…As output parameters, surface roughness, kerf taper angle, and material removal rate will also be the focus of this survey, as well as the phenomenon of delamination, a summary of the relationship between these two and input parameters. It is noteworthy that the AWJM uses erosion to remove the target material, so there is no contact between the cutting tool and the material, and there are no high impact defects of cutting forces related to delamination damage [ 13 , 18 ], but strength of NFRPs machined by AWJM gets affected, so the tensile strength is somewhat lesser than the composites cut by traditional methods [ 13 ].…”
Section: Cutting Processes Of Natural Fiber-reinforced Polymer Commentioning
confidence: 99%
“…[ 2 , 4 , 6 , 7 , 8 ]. Although the NFRP composites are manufactured near-net shape, they still need some final cutting processes to reach the shape required such as drilling, cutting, and trimming processes [ 9 , 10 , 11 , 12 , 13 , 14 ]. Composite materials do not behave like conventional materials under different cutting processes, because of their different properties.…”
Section: Introductionmentioning
confidence: 99%
“…These reinforcements have proved to be the best in respect to the mechanical strengths and durability. 33,34 A research on the influence of lanthanum salt treatment on the poly- p -phenylenebenzobisoxazole FRPs revealed that the surface treatment enhanced the amount of polar groups and improved the adhesive bonding between the fibre and matrix as a result, the friction coefficient and wear rate are considerably alleviated. 35 The addition of micro-sized particles in the composite matrix enhances the resistance to friction and wear.…”
Section: Tribological Behaviour Of Artificial Frpmentioning
confidence: 99%
“…Extensive reviews on static mechanical, [10][11][12] tribological, 13,14 dynamic mechanical thermal analysis, 15 machining, 16 flammability and flame retardant properties, 17 of NFRC are found at literature database, but review on vibration damping studies of natural fiberreinforced composites is not yet reported. To the best of our knowledge, this would be the first attempt to bring together the vibration studies, by experimental and numerical methods, on natural fiber-reinforced thermoset and thermoplastic polymer matrix composites to promote the researchers and industrialist towards vibrational response of NFRC.…”
Section: Introductionmentioning
confidence: 99%